Response of Maize Plant Growth Due to Application of Liquid and Solid (Microbeads) Diazotroph Endophytic Bacteria Biofertilizer (Respon Pertumbuhan Tanaman Jagung Akibat Aplikasi Pupuk Hayati Cair dan Padat (Microbeads) Bakteri Endofitik Diazotrof) - Regina Teuresna Dewi; Mieke Rochimi Setiawati; M. Julio Ferdiansyah; Eki Riftahur Rizki; Nadia Nuraniya Kamaluddin; Pujawati Suryatmana; Anne Nurbaiti; Reginawanti Hindersah; Betty Natalie Fitriatin; Rangga Jiwa Wibawa (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2026)
This study aimed to evaluate the effect of diazotrophic endophytic bacteria inoculation in liquid and microbeads formulations on the vegetative growth of maize (Zea mays L.). The experiment was conducted from September 2025 to March 2026 at the Soil Biology Laboratory and Ciparanje Experimental Field, Faculty of Agriculture, Universitas Padjadjaran. The study used a Randomized Block Design consisting of seven treatments and four replications. Treatments included liquid and microbeads biofertilizers containing Gluconacetobacter diazotrophicus strain GD 3-1, Paraburkholderia sp. strain GD 12-2, and their consortium. Observed parameters included plant height, stem diameter, leaf area, intensity of plant pest disturbance, and stem endophytic bacterial population. Data were analyzed using analysis of variance (ANOVA) followed by the Scott-Knott test at a 5% significance level using Statistical Package for the Social Sciences (SPSS) 21. The results showed that biofertilizer application significantly affected maize growth at the late vegetative stage. Liquid formulation of G. diazotrophicus produced the highest plant height at 8 weeks after planting, while microbeads formulation showed more stable growth responses during the observation period. Biofertilizer treatments also increased leaf area and stem endophytic bacterial population compared with the control treatment. In addition, inoculated plants showed better tolerance to pest attacks during the vegetative stage. Overall, the application of diazotrophic endophytic bacteria, particularly G. diazotrophicus, demonstrated potential to improve maize vegetative growth and support sustainable agricultural practices.